The Influence Of Listening To English Songs TowardVocabulary Mastery Of Second Year Student Of SMUN I Grabag Magelang - Setyawati, Ike (2004)
The research is aimed to know: 1) The Influence of listening to English songs toward the students' vocabulary mastery, 2) The result of listening to English songs toward the students' vocabulary mastery. The research is undertaken in SMUN 1 of Grabag Magelang. The population in the research is 2nd grade students of SMUN 1 of Grabag Magelang. The samples are selected using simple random sampling technique. The data collection method is using three ways, observation, questionnaire and documentation. Data analysis is done using regression analysis with an independent variable. The result of the research shows that: 1) There is a positive and significant influence of listening to English songs toward the students' vocabulary mastery in SMUN 1 of Grabag Magelang, is can be seen from the t-test result with the value of tcal = 3.064 > ttabel = 2.0315; 2) The regression coefficient (r) gained is 0.644 and r2 = 0.528. is mean that listening to English songs may determine the vocabulary mastery on students about 52.80%.